Ten new temperate bacteriophages of Citrobacter youngae - Smarda, J; Slovácková, H (Folia microbiologica, 2004)
In a cross-test, we examined 55 strains of Citrobacter youngae against each other as potential producers of temperate bacteriophages and as potential sensitive indicators for them. Ten strains (18.2 %) showed the production of phages. Seven different strain-specific spectra of activity (from 1 to 11 strains each) were found. Phage production by 6 strains was inducible with mitomycin C, in 4 strains it was not inducible. The plaques of the phages were more or less turbid, without a lytic halo, tiny to small, 0.2-1.3 mm in diameter. Using a polyclonal, specific anti-lambda serum, all 10 phages were found to be clearly distinct from E. coli lambda phage, the phage 31/47 showing the highest neutralization titre of all. Interspecific tests with 15 strains of 8 species of Enterobacteriaceae revealed not a single case of activity of Citrobacter phages towards any of them. Five phage-immune clones lysogenized with 5 of the phages kept their remaining phage sensitivity spectra, though extended by sensitivity to 1-3 phages; 2 of these strains acquired also sensitivity to phage lambda. The phages belong to the morphotypes of Myoviridae (6 phages) and Siphoviridae (4 phages), with head diameters of 51-58 nm and tail length of 97-173 nm. Three strains produced corpuscular bacteriocins.
Keywords: lyzogenie; mitomycin; aktivace viru; Lysogeny; Citrobacter; Mitomycin; Bacteriophages; bakteriofágy; Bacteriophage Typing; fagotypizace; Virus Activation